(untitled) - Fix, John D. (New York, 2006)
This is a text for an introductory astronomy course. One of the main goals is to give a broad and deep enough background in astronomy so that students will be able to follow current developments in the subject years after they complete the course. This book presumes that most of its readers are not science majors and that they probably have not had a college-level science or mathematics course. It gives a complete description of current astronomical knowledge, although not at an extreme technical level nor in a way that fails to communicate the quantitative nature of physical science. Finally, the historical development of astronomy is emphasized to show that astronomy, like other sciences, advances through the efforts of many scientists, and to show how present ideas have been developed. - The book includes up-to-date results for the Mars Global Surveyor, with discussion of distant supernovas and the cosmological constant.
Keywords: Astronomy,Thiên văn học; Sách giáo khoa